Traces and Modern Islamic Thought in Southeast Asia: Malaysia, Pattani and Mindanao - Asman Asman; Tamrin Muchsin (Universitas Darussalam Gontor, 2022)
This study talks about the ethnicity of the Southeast Asian community known as Malay Muslims. However, in the trail of pedestrians there are social gaps that are influenced by mindsets and politics that cause Muslims to be divided so that they are marginalized in certain countries, especially in Asian countries. Islamic historians argue that Southeast Asian Islam is categorized as a cultural area that is quite influential from the seven regions of Islamic culture in the world, such as Malaysia, Pattani and the Philippines. The focus in this discussion is How are Modern Islamic Traces and Thoughts in Malaysia, Pattani (Thailand) and in Mindanou (Philippines)?. The method used in this study is a qualitative type of literature while the approach used in this study is a historical approach. The results of this study are the occurrence of tensions between Malay Muslims in Malaysia, Thailand and the Philippines is caused by religious, ethnic, cultural and political issues brought into the state so that the conflict is getting hotter and until now there is no solution for peace for Asian countries that conflicted.